Max Scheler e Lima Vaz: A dimensão antropológica do Espírito - de Sousa, Maria Celeste (Kairós: Revista Acadêmica da Prainha, 2021)
The article compares how Max Scheler and Lima Vaz present the transcendental and unifying category of the Spirit as a constitutive dimension of anthropological discourse. The first topic presents the dialogue that the two philosophers have with the metaphysical tradition and the method chosen in the act of philosophizing in the present time. In the second topic we discuss the unveiling of the spirit in anthropological discourse, evidencing man as a spiritual being, and in the third topic the relation of man to transcendence is presented.